Designing a Knowledge-Based Performance Management System for PT WLL - Steven Nathanael Setiawan; Dermawan Wibisono (Green Publisher Indonesia, 2026)
PT WLL was an Indonesian food manufacturing company that had produced soy sauce and condiments for several decades. Despite its long operational history, the company experienced performance challenges, including declining sales, inefficient processes, and limited employee capability. These issues largely emerged from the absence of an integrated performance management system that connected financial and non-financial indicators. The objective of this study was to design a Knowledge-Based Performance Management System (KBPMS) that aligned with PT WLL’s strategic and operational needs. A mixed-methods approach was applied. Qualitative data were collected through semi-structured interviews and focus group discussions with managers and the director, while secondary data were obtained from company records, production reports, and financial documents. Porter’s Five Forces, VRIO, and the Current Reality Tree (CRT) were used to diagnose systemic performance gaps. The KBPMS framework guided the development of a performance structure consisting of three perspectives: business results, internal processes, and resource capabilities. The Analytical Hierarchy Process (AHP) was used to prioritize key performance indicators (KPIs) through expert pairwise comparisons. The findings revealed that the company faced three primary challenges: weak interdepartmental coordination, outdated operational processes, and a lack of integrated performance metrics. The proposed KBPMS offered structured performance measurement, clearer strategic alignment, and knowledge-sharing mechanisms. Implementing the system was expected to improve PT WLL’s financial stability, process reliability, and employee competency. The study made theoretical and practical contributions by demonstrating how KBPMS could be adapted for medium-sized food manufacturing firms to strengthen their competitiveness and long-term sustainability.